Methodological and ethical challenges in investigating nurses’ experiences of medication errors - Αthanasakis, Εfstratios (2018)
The present dissertation is about registered nurses’ experiences of medication errors (MEs) which are approached as lived phenomena. A meta-synthesis (systematic review of qualitative evidence) of nurses’ experiences of MEs is presented first, followed by a relevant research proposal to investigate them with interpretative phenomenological analysis (IPA), a reflexive chapter about the methodological and ethical challenges for their investigation and finally a Doctor of Philosophy (PhD) research proposal is presented. The meta-synthesis included eight studies and was conducted by using thematic synthesis. The focus is gathered exclusively on nurses’ experiences of MEs which were approached as lived phenomena. The themes and subthemes that emerged out from the synthesis were six and twenty, respectively. The themes were: ‘moral and emotional impact’, ‘constructive learning’, ‘impact on professional registration and employment’, ‘nurses’ coping strategies with the experience’, ‘patient and family’ and ‘identification of contributing factors of and preventive measures for MEs’. The review contributes to the understanding of nurses’ making sense of experiences of MEs and towards to this direction a holistic view about the value and dimensions of the experience itself is provided. As frontline nurses are responsible for the medication administration to patients, the moral and emotional impact of the errors is devastating for their professional identity, employment status, and personal life. Yet, the experience of MEs by nurses poses a constructive aspect and nurses detect strategies to cope with the error occurrence and its consequences. They also detect ways to translate their experience into a beneficial and constructive lesson for themselves, their practice and the organisation they work for. The meta-synthesis revealed that none of the previous studies used IPA to explore nurses’ experiences of MEs and only a few studies focused exclusively on their meaning. Thereby, a research proposal presents the rationale for using IPA, methods, methodological and ethical challenges that such a study entails. However, within the context of the master course, it was impossible to achieve ethical approval to carry out the proposed study and a reflexive chapter about the methodological and ethical challenges faced is developed instead. Examples of the challenges faced concerned nurses’ recruitment and management of emotionality during the interview. The above research proposal and reflections about the methodological challenges led to the formation of a future PhD proposal of a qualitative interviews design study combined with characteristics of IPA. Finally, the dissertation concludes with implications for further research.